A copula-TGARCH approach of conditional dependence between oil price and stock market index: The case of Mexico - Lorenzo Valdés, Arturo; Armenta Fraire, Leticia; Durán Vázquez, Rocío (Estudios Económicos de El Colegio de México, 2016)
This study applied the Clayton and Gumbel copulas using the TGARCH model for marginal distribution of returns in order to describe the tail dependence between oil prices and the Mexican stock market index (IPC, Index of Prices and Quotations) on a weekly basis, from 2010 to 2014. We found that each of the analyzed series of stock index and oil returns can adequately be described with the proposed TGARCH model, and that there is some degree of conditional dependence in the tails, with greater volatility on the upper (right) tail and more stability on the lower (left) tail.